Genome-wide analysis of the WOX gene family and the role of EjWUSa in regulating flowering in loquat (Eriobotrya japonica) - Yu, Yuanhui; Yang, Miaomiao; Liu, Xinya; Xia, Yan; Hu, Ruoqian; Xia, Qingqing; Jing, Danlong; Guo, Qigao (Frontiers in Plant Science, 2022)
The WUSCHEL (WUS)-related homeobox (WOX) gene family plays a crucial role in the shoot apical meristem formation, embryonic development, stem cell maintenance, and various other developmental processes. However, the identification and function of WOX genes have not been reported in perennial loquat. In this study, 18 EjWOX genes were identified in loquat genome. Chromosomal localization analysis showed that 18 EjWOX genes were located on 12 of 17 chromosomes. Gene structure analysis showed that all EjWOX genes contain introns, of which 11 EjWOX genes contain untranslated regions. There are 8 pairs of segmental duplication genes and 0 pairs of tandem duplication genes in the loquat WOX family, suggesting that segmental duplications might be the main reason for the expansion of the loquat WOX family. A WOX transcription factor gene named EjWUSa was isolated from loquat. The EjWUSa protein was localized in the nucleus. Protein interactions between EjWUSa with EjWUSa and EjSTM were verified. Compared with wild-type Arabidopsis thaliana, the 35S::EjWUSa transgenic Arabidopsis showed early flowering. Our study provides an important basis for further research on the function of EjWOX genes and facilitates the molecular breeding of loquat early-flowering varieties.